EVALUASI PRODUKSI STAGGERED CREW DI TAMBANG BAWAH TANAH DEEP ORE ZONE PT. FREEPORT INDONESIA - Gianfranco Enrico Pocerattu; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
To increased the production, the Deep Ore Zone (DOZ) mining department has a concept of implementing a staggered crew. Staggered crew is a crew formed specifically to support production activities. To assess the performance of the application of the staggered crew, an evaluation of the factors that influence production activities is carried out. Factors that subject to evaluation are working time, number of operators and production capability. The results of evaluating work time (optimum efficiency) for crew I, II, and III showed as follow 29%, 30%, and 28% respectedly. Very low efficiency is due to time constraints in operation, which are affected by delay time, idle time and maintenance time. Average productive work time (work) is 3.26 hours/day, delay time is 3.26 hours/day, idle time is 4.03 hours/day and maintenance time is 0.53 hours/day. Idle time is the highest time of these four parameters. The results also showed that there were differences in the number of distribution operators, namely crew I numbered 16 people, crew II numbered 12 people and crew III numbered 15 people. But the number of operators on each crew is still sufficient to support production activities. The average production is 62.14 tons/hour and 4,784.78 tons/day. So with a production of 62.14 tons/hour and working time of 11 hours/day, it takes a minimum of 8 dump truck operators to reach a value of 5,468.32 tons/day.